Aberdeen Angus - Morrison, Orr O. (My University, 1908)
Introduction: In making a study of any breed of stock it always appears necessary to make a statement, either brief or lengthy, of the history of that particular breed before entertaining into any discussion of characters and qualities. It is the purpose, then, in handling the subject however broad it may be, to give a brief history of the breed…
Citation: Morrison, Orr O. Aberdeen Angus. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Cattle; Aberdeen Angus; Breeding; Graduating theses; Senior theses; Theses